The Effectivity Of Empathic Love Therapy To Increase Subjective Well-Being And Teacher Readiness In Inclusive School - Rosada, Admila (UIN Sunan Kalijaga Yogyakarta, 2019)
Inclusive education has been done in Indonesia since Law on the National Education System Number 20 the year 2003 is declared. Implementation evaluation of this inclusive education shows that teacher’s readiness in conducting inclusive classroom is still in a low level, whereas the teacher is one of the four pillars in education. The teacher feels hard to facilitate special educational needs children, so influence his/her subjective wellbeing. The education ministry has organized some technical training about inclusive education. Some research shows that the training is only focused on the theory, regulation, and technical implementation, so no session facilitates the teacher’s affection domain. Empathic Love Therapy is a therapy series with a transpersonal approach to recognize self. This research aims to know the effectiveness of Empathic Love Therapy in increasing teacher subjective wellbeing and readiness in inclusive school settings. Research instrument to collecting data uses subjective wellbeing scale and teacher readiness scale. The subjects in this research are ten shadow teachers from Yogyakarta Inclusive School Forum. The result of this research shows that Empathic Love Therapy is useful in increasing teacher subjective wellbeing, but it is not sufficient to increase teacher’s readiness to conduct inclusive classrooms. The description of this result is explained in the discussion chapter.